Benzoic acid-2-{(E)-[(E)-2-(2-pyridylmethylidene)hydrazin-1-ylidene]methyl}p yridine (2/1) - Arman, Hadi D.; Kaulgud, Trupta; Tiekink, Edward R.T. (International Union of Crystallography, 2010)
The asymmetric unit of the title cocrystal, C12H10N4 center dot 2C(7)H(6)O(2), comprises a single molecule of benzoic acid and one half-molecule of 2-pyridinealdazine situated about a centre of inversion. The carboxyl group is coplanar with the benzene ring to which it is connected [O-C-C-C = -172.47 (12)degrees] and similarly, the 2-pyridinealdazine molecule is planar (r.m.s. deviation of the 16 non-H atoms = 0.017 angstrom). In the crystal, molecules are connected into a non-planar three-molecule aggregate [dihedral angle between the benzene and pyridyl ring connected by the hydrogen bond = 61.30 (7)degrees] with a twisted Z-shape. Layers of 2-pyridinealdazine molecules in the ab plane are sandwiched by benzoic acid molecules being connected by O-H center dot center dot center dot N and C-H center dot center dot center dot O interactions, the latter involving the carbonyl O atom so that each benzoic acid molecule links three different 2-pyridinealdazine molecules. Interdigitated layers stack along the c axis.